Analisis Kepuasan Konsumen Dengan Persepsi Harga, Kualitas Produk dan Kualitas Pelayanan sebagai Variable Yang Mempengaruhinya pada Restoran Seribu Rasa Jakarta - Syathibi Al Mathari; Aris Budiono (LPPM Universitas Asa Indonesia, 2022)
This study aimed to determine the effect of price perception, product quality and service quality on consumer satisfaction and how it develops. Survey data was taken in May 2022 on the consumers of the Seribu Rasa restaurant in Jakarta as many as 130 respondents using the accidental sampling method. From 130 respondents, as many as 30 respondents we processed for validity and reliability testing, our multiple linear regression analysis used 100 respondents in the calculation. The F-test was conducted to see whether the independent variable had a combined effect on the dependent variable. Partially we use a t-test to test each independent variable on the dependent variable. The conclusion of this study answers the following hypothesis: together, all the independent variables, namely: price perception, product quality and service quality, can affect the dependent variable called consumer satisfaction partially two variables, namely product quality and service quality, can affect consumer satisfaction, and one variable, namely price perception does not affect consumer satisfaction variable Keywords: Consumer Satisfaction, Price Perception, Product Quality, Service Quality